Simultaneous and cumulative effects of tDCS on cerebral metabolic rate of oxygen in multiple sclerosis - Muccio, Marco; Pilloni, Giuseppina; Walton Masters, Lillian; He, Peidong; Krupp, Lauren; Datta, Abhishek; Bikson, Marom; Charvet, Leigh; Ge, Yulin (Frontiers in Human Neuroscience, 2024)
Introduction: Transcranial direct current stimulation (tDCS) is a non-invasive neuromodulation technique with simultaneous (during stimulation) and cumulative effects (after repeated sessions) on blood flow and neuronal metabolism. These effects remain mostly unclear especially in multiple sclerosis (MS). This work aims to elucidate brain metabolic and hemodynamic underpinnings of tDCS and its potential therapeutic impact in MS patients using quantitative tDCS-MRI.Methods: MS participants (n=20; age=45.4±12.3 years, 7 males) underwent 3T MRI scans before and after 20 daily sessions of dorsolateral prefrontal cortex (DLFPC) tDCS (2.0mA, left anodal) paired with adaptive cognitive training (aCT). During both visits, imaging measurements of cerebral blood flow (CBF), cerebral venous blood oxygenation (Yv) and calculated cerebral metabolic rate of oxygen (CMRO2) were obtained at pre-tDCS, during-tDCS and post-tDCS.Results: At baseline, significant increase from pre-to during-tDCS was observed in CMRO2 (7.6%;p=0.002), CBF (11.0%; p<0.0001) and Yv (1.9%; p=0.006). At follow up, we observed an increase in pre-tDCS CMRO2 (140.59±13.83 µmol/100g/min) compared to baseline pre-tDCS levels (128.30±14.00 µmol/100g/min; p=0.006). Sustained elevations in CMRO2 and CBF into post-tDCS were also observed (tDCS lingering effects). Cumulative tDCS effects were observed in the form of sustained elevations in CMRO2 and CBF in pre-tDCS follow up, reaching the magnitudes measured at baseline during-tDCS.Discussion: TDCS induces an acute surge in metabolic activity persisting immediately after the stimulation is removed. Moreover, treatment composed of repeated tDCS-aCT paired sessions contributes to establishing long-lasting increases in neuronal activity.